Nuclear medicine imaging methods of early radiation-induced cardiotoxicity: a ten-year systematic review - Eber, Jordan; Blondet, Cyrille; Le Fevre, Clara; Chambrelant, Isabelle; Hubele, Fabrice; Morel, Olivier; Antoni, Delphine; Noel, Georges (Frontiers in Oncology, 2023)
Radiotherapy has significantly improved cancer survival rates, but it also comes with certain unavoidable complications. Breast and thoracic irradiation, for instance, can unintentionally expose the heart to radiation, leading to damage at the cellular level within the myocardial structures. Detecting and monitoring radiation-induced heart disease early on is crucial, and several radionuclide imaging techniques have shown promise in this regard. In this 10-year review, we aimed to identify nuclear medicine imaging modalities that can effectively detect early cardiotoxicity following radiation therapy. Through a systematic search on PubMed, we selected nineteen relevant studies based on predefined criteria. The data suggest that incidental irradiation of the heart during breast or thoracic radiotherapy can cause early metabolic and perfusion changes. Nuclear imaging plays a prominent role in detecting these subclinical effects, which could potentially serve as predictors of late cardiac complications. However, further studies with larger populations, longer follow-up periods, and specific heart dosimetric data are needed to better understand the relationship between early detection of cardiac abnormalities and radiation-induced heart disease.